The potential distribution of bioenergy crops in Europe under present and future climate - Tuck, Gill; Glendining, Margaret J.; Smith, Pete; House, Jo I.; Wattenbach, Martin (Biomass & bioenergy, 2006)
We have derived maps of the potential distribution of 26 promising bioenergy crops in Europe, based on simple rules for suitable climatic conditions and elevation. Crops suitable for temperate and Mediterranean climates were selected from four groups: oilseeds (e.g. oilseed rape, sunflower), starch crops (e.g. potatoes), cereals (e.g. barley) and solid biofuel crops (e.g. sorghum, Miscanthus). The impact of climate change under different scenarios and GCMs on the potential future distribution of these crops was determined, based on predicted future climatic conditions. Climate scenarios based on four IPCC SRES emission scenarios, A1FI, A2, B1 and B2, implemented by four global climate models, HadCM3, CSIRO2, PCM and CGCM2, were used. The potential distribution of temperate oilseeds, cereals, starch crops and solid biofuels is predicted to increase in northern Europe by the 2080s, due to increasing temperatures, and decrease in southern Europe (e.g. Spain, Portugal, southern France, Italy, and Greece) due to increased drought. Mediterranean oil and solid biofuel crops, currently restricted to southern Europe, are predicted to extend further north due to higher summer temperatures. Effects become more pronounced with time and are greatest under the A1FI scenario and for models predicting the greatest climate forcing. Different climate models produce different regional patterns. All models predict that bioenergy crop production in Spain is especially vulnerable to climate change, with many temperate crops predicted to decline dramatically by the 2080s. The choice of bioenergy crops in southern Europe will be severely reduced in future unless measures are taken to adapt to climate change.